Hubungan Pengetahuan Tentang Kanker Payudara Terhadap Sikap Remaja Putri Dalam pencegahan Kanker Payudara - Azzahra, Fhatimah (Jurnal Kesehatan Ilmiah Aufa Royhan, 2022)
Teenager girls’ knowledge of breast cancer affects their attitudes toward breast cancer prevention, which young women subsequently address as positive and negative reactions. This study intended to determine the relationship between knowledge about breast cancer and the attitude of teenager girls in preventing breast cancer at SHS 8 Pekanbaru. This study used a descriptive correlation design with a cross sectional approach. The research sample consisted of 81 persons who were chosen using a stratified random sampling technique based on inclusion criteria. The analysis used is bivariate analysis using the chi-square test. Statistical tests revealed no significant correlation between knowledge about breast cancer and teenager girls’ attitudes toward breast cancer prevention. With p-value (0,241) > Alpha (0,05). There was no significant relationship between teenager girls’ attitudes toward breast cancer prevention. It is recommended for teenanger girls to perform early detection by conducting a self-examination (SADARI) or can perform a clinical examination (SADANIS).